Pengaruh Layanan Bimbingan Klasikal Terhadap Kemandirian Belajar Peserta Didik Kelas X SMAN 6 Semarang - Rahman, Arif Khalilu; Setianingsih, Eka Sari; Ismanto, Heri Saptadi; Respati, Ardiatma Rio (Indonesian Journal of Educational Counseling, 2024)
This research seeks to explore the impact of classical guidance services on the learning independence of tenth-grade students at SMAN 6 Semarang. Using a quantitative experimental method, this research examines whether there is a significant impact of classical guidance services on students' learning independence. The study involved a sample of 43 students selected through simple random sampling. Data was collected using a Likert-scale questionnaire assessing learning independence. The experimental design included a one-group pretest-posttest approach. Results showed that prior to the classical guidance intervention, 79.1% of students exhibited low learning independence. Post-intervention, there was a notable improvement, with 20.9% of students reaching a moderate level. The paired sample t-test indicated a significant difference in learning independence before and after the intervention (sig = 0.000 < 0.05). Results of the paired sample t-test analysis revealed a significant positive impact of classical guidance services on learning independence. Additionally, the calculation of a normalized gain score of 0.72 indicates that classical guidance services are effective in enhancing students' learning independence. This study supports previous research indicating that classical guidance services effectively increase students' motivation, concentration, and self-confidence. In conclusion, classical guidance services contribute significantly to developing students' potential and achieving developmental tasks, particularly in fostering independent learning within the school environment.